Boosting the photocatalytic hydrogen evolution performance via an atomically thin 2D heterojunction visualized by scanning photoelectrochemical microscopy. (November 2019) - Lee, Jae Yoon; Kang, Sungwoo; Lee, Donghun; Choi, Seokhoon; Yang, Seunghoon; Kim, Kangwon; Kim, Yoon Seok; Kwon, Ki Chang; Choi, Soo ho; Kim, Soo Min; Kim, Jihoon; Park, Jungwon; et al.
Abstract: Heterojunction catalyst can facilitate efficient photoelectrochemical (PEC) hydrogen evolution by reducing a potential barrier for charge transfer at the semiconductor/electrolyte interface. Such a heterojunction effect at the atomic thickness limit has not yet been explored although it can be strengthened because of strong built-in field and ultrafast charge transfer across the junction. Here, we first investigate a novel strategy to boost the hydrogen evolution performance of the p -type WSe2 photocathode via reducing the overpotential with an atomically thin heterojunction catalyst comprising MoS2 and WS2 monolayers. To unveil an effective role of the heterojunction by isolating its kinetic contribution from other collective catalytic effects, we develop and utilize an in situ scanning PEC microscopy, which enables the spatially-resolved visualization of the enhanced photocatalytic hydrogen evolution performance of the heterojunction. Notably, significant reduction in overpotential, from +0.28 ± 0.03 to −0.04 ± 0.05 V versus (vs.) the reversible hydrogen electrode (RHE), is achieved when the MoS2 /WS2 heterojunction is introduced as a catalyst even without intentional generation of catalytic sites. As a result, the photocurrent of ~4.0 mA cm −2 occurs even at 0 V vs. RHE. Furthermore, the beneficial effect of the atomically scaled vertical heterojunction is explained by the built-in potential resulted from efficient charge transfer in type-II heterojunctions with the support of first-principles calculations. Our demonstration not only offers an unprecedented approach to investigating the fundamental PEC characteristics in relation to the tailored properties of a catalyst but also proposes a new catalytic architecture, thereby enabling the design of highly efficient PEC systems. Graphical abstract: Utilizing the atomically thin 2D heterojunction as a catalyst, the significant enhancement of the photocatalytic hydrogen evolution performance is achieved via reducing overpotential without intentional generation of catalytic sites. The scanning photoelectrochemical microscopy enables the spatially-resolved visualization of the enhanced performance of the heterojunction while isolating its kinetic contribution from other collective catalytic effects.Image 1 Highlights: Atomically thin heterojunction catalyst is realized by staking MoS2 and WS2 monolayers on the p -type WSe2 photocathode. Significant reduction in overpotential, from +0.28 ± 0.03 to −0.04 ± 0.05 V vs. RHE, is achieved. The enhanced HER is visualized by in situ scanning photoelectrochemical microscopy.